Litter Size and Lamb Survivability of Batur Sheep in Upland Areas of Banjarnegara Regency, Indonesia - Sodiq, A; Yuwono, P; Santosa, SA (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2011)
Abstract. The objective of the current study was to find out the litter size and lamb survivability of Batur sheep, and also to identify the effects of ewe parities on litter size and lamb survivability; and the effects of birth type on lamb survivability of Batur sheep. The study was conducted at the Batur sheep Farming Group in the upland areas of Banjarnegara regency, Central Java province of Indonesia. Data from 311 records of lambing of Batur sheep at the village breeding centre for Batur sheep were analyzed. Least squares procedure by the General Linear Model was used to identify the effect of parity on litter size at birth and at weaning. Preweaning survivability was analyzed using the Chi-squares. Results showed that average litter size at birth and at weaning, and lambs survivability till weaning were 1.55±0.03 and 1.36±0.03 lambs; and 88.42%, respectively. Litter size at weaning and lambs survivability was significantly different among ewe parities, and increased by advancing ewes parities. Its indicating that age of ewe was important factor for the success in early stage for producing lamb. Survivability of single lamb (93.62%) was significantly higher that twins (84.11%). Increased care for twins by providing proper management might lead to a recognizable increase in lamb survival and flock productivity of Batur sheep.Key words: Batur sheep, litter size, lamb survivability, parity, preweaningAnimal Production 13(3):166-172 (2011)